Epidemiological Profile of Pregnant Women with Anemia Admitted at the Maternity Unit of the Health District Hospital of Keita, Tahoua from 2018 to 2020 - , Maman Manzo Lawaly; , Minou Ibrahim; , Karimou Harouna Boureima; , Zoubeirou Alzouma Mayaki (Archives of Current Research International, 2023)
Aims: The objective of this study is to provide data on the epidemiological profile of pregnant women aged 15-45 years with anemia in Keita department, Tahoua regional state of Niger republic. Methodology: A retrospective cross-sectional study was conducted from January 1st, 2018 to December 31st, 2020, on pregnant women who attended antenatal care at the maternity unit of the health district of Keita. Structured questionnaire was used to retrieve data regarding pregnancy from the medical record files which are archived at the maternity unit and entered into Epi Info version 7.2.4.0 for further analysis. Results: Of the 1571 registered pregnant women, 310 suffered from anemia, with the prevalence of 19.7%. The prevalence of the severity of anemia was 17.7% mild, 49.0% moderate, and 33.2% severe anemia. The mean age of the pregnant women with anemia was 25.3±6.97 years and most were at third trimester (53.5%). Out of 310 patients, 244(78.7%) were either illiterate or had primary education level. Most of them 262(84.5%) are housewives and only 2(0.7%) visited hospital for antenatal care more than four times. About 249(80.3%) were multigravida. 52(16.8%) deliveries were by cesarean section with a higher recourse to blood transfusion. Major maternal complications were postpartum hemorrhage (28.4%), abortion (31.9%), malaria (15.2%) and maternal deaths (5%). Neonatal outcome was analyzed in terms of stillbirth (9%) and neonatal deaths (7%). Conclusion: Anemia in pregnancy is a real public health problem in Niger republic and was mild in severity in the study setting of Keita, especially during the third trimester. Pregnant women who were younger, housewives, illiterates, multiparous and multigravida constitute the most vulnerable segments of the population at risk of anemia. Therefore, further strengthening of the existing health care system through awareness and education on early and regular antenatal care visits for a positive pregnancy experience should be reinforced.